The prevalence of IgG antibodies against milk and milk antigens in patients with multiple sclerosis - Chunder, Rittika; Heider, Thorsten; Kuerten, Stefanie (Frontiers in Immunology, 2023)
Multiple sclerosis (MS) is a chronic demyelinating disease of the central nervous system (CNS). The pathophysiology of MS is complex and is said to be influenced by multiple environmental determinants, including diet. We and others have previously demonstrated how consumption of bovine milk can aggravate disease severity in MS patients, which can be explained by molecular mimicry between milk antigens and those expressed within the CNS. In this study we set out to identify alternatives to drinking cow milk which might be less detrimental to MS patients who have a genetic predisposition towards developing antibody titers against bovine milk antigens that cross-react with CNS antigens. To this end, we screened 35 patients with MS and 20 healthy controls for their IgG reactivity against an array of animal-sourced milk, plant-based alternatives as well as individual antigens from bovine milk. We demonstrate that MS patients have a significantly higher IgG response to animal-sourced milk, especially cow milk, in comparison to healthy donors. We also show that the reactivity to cow milk in MS patients can be attributed to reactivity against different bovine milk antigens. Finally, our correlation data indicate the co-existence of antibodies to individual bovine milk antigens and their corresponding cross-reactive CNS antigens. Taken together, we suggest screening of blood from MS patients for antibodies against different types of milk and milk antigens in order to establish a personalized diet regimen.